Assess the level of functional adaptation according to some indicators of blood during the period of competition among advanced handball players applicants - Ayad, Amena (Journal of Physical Education, 2014)
The period of the competition is keeping of the player on the level of performance through training where the training have an impact in the chemical reactions in the blood which has emerged these influences physiological on the training process, as it has become an indicator for measuring the functional status and training of the handball players before the competition, and after that , to see the potential for adaptation career the level of endurance and its impact on the player, but the problem of the research lies in the assessment of the level of adaptation career during the competitions using enzymatic (CPK) in the blood, and touched goals which are determined the level of adjustment career according to some indicators of blood during the competitions and assess the level of adjustment career according to some indicators of blood during the period of competition among players Handball applicants. The imposition of a text of the research confirms that there were statistically significant differences between pre and post tests for some of the indicators of blood in the competitions. Through part II, the theoretical study has adapted the concept of functional and enzymatic (CPK) in the blood. While In the third chapter, the researcher has depended and used the experimental method on a sample of applicants reel players and hand numbered (10) players. Part IV bag researcher which has used the statistical (SPSS) and the results were fully discussed, relying on the scientific sources. In Part V the fifth part the researcher confirms that the period of the competition, which had a duration of 80 days was enough to influence on the indicators of blood and the researcher has recommended to the attention of coaches when developing training programs using scientific methods based on the results of laboratory tests certified as a case of the evaluation of training and knowledge of the health status of athletes